Effects of different fertilization rates on growth, yield, quality and partial factor productivity of tomato under non-pressure gravity irrigation. - Qing-Jie Du; Huai-Juan Xiao; Juan-Qi Li; Jia-Xin Zhang; Lu-Yao Zhou; Ji-Qing Wang (PLoS ONE, 2021)
To select the optimum fertilizer application under specific irrigation levels and to provide a reliable fertigation system for tomato plants, an experiment was conducted by using a microporous membrane for water-fertilizer integration under non-pressure gravity. A compound fertilizer (N:P2O5:K2O, 18:7:20) was adopted for topdressing at four levels, 1290 kg/ha, 1140 kg/ha, 990 kg/ha, and 840 kg/ha, and the locally recommended level of 1875 kg/ha was used as the control to explore the effects of different fertilizer application rates on growth, nutrient distribution, quality, yield, and partial factor of productivity (PFP) in tomato. The new regime of microporous membrane water-fertilizer integration under non-pressure gravity irrigation reduced the fertilizer application rate while promoting plant growth in the early and intermediate stages. Except for the 990 kg/ha fertilizer treatment, yields per plant and per plot for each fertilizer application rate were higher than or equal to those of the control. The new regime could effectively improve PFP and reduce soil nutrient enrichment. Fertilizer at 840 kg/ha showed the optimum results by increasing PFP by 75.72% as compared to control. In conclusion, the fertilizer rate at 840 kg/ha has not only maintained the productivity of soil but also tomato growth and quality of fruit which makes the non-pressure gravity irrigation a potential and cost-effective way for fertilizer application.